Parasitological status of dairy cattle in Votuporanga and Valentim Gentil, SÃ£o Paulo State, Brazil - Giane Serafim da Silva; Daiane Mompean Romera; Daniele Costa Araújo; Renato Augusto Pereira da Silva; Ricardo Alexandre Gomes (Boletim de Indústria Animal, 2012)
Given the importance of nematode parasites in cattle herds, this study aimed to assess the parasitological status of dairy cattle from small producers in Votuporanga and Valentim Gentil, SP. During technical visits to 45 farms in the region, interviews and stool sample collections were performed. It was observed that the producers of the area follow different treatment programs and did not follow specific recommendations of any official institution or organ. It is noteworthy that the producers choose the medication according to their own guidance or at the shop counter, and use mainly ivermectin and doramectin to treat animals. Results of fecal examinations revealed higher values of EPG in lactating animals, followed by weaned animals. The stool cultures showed that infection was caused mainly by Haemonchus sp and Cooperia sp., and also that cattle of all farms were positive for Eimeria spp., while the most infected were lactating and weaned animals.